1985
DOI: 10.1002/1097-0142(19851215)56:12<2789::aid-cncr2820561213>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on human natural killer cell activity

Abstract: Natural killer (NK) cells play a central role in immune surveillance against tumors and viral infections. NK activity is depressed in patients who have a wide range of carcinomas, including carcinomas of the lung. Peripheral blood NK activity was measured in 22 nonsmokers, 15 light/moderate smokers, 12 heavy smokers, and 19 patients with carcinoma of the lung. Patients with carcinoma of the lung had marked depression in NK activity compared with nonsmokers. Light/moderate smokers had NK activity comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
3

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 13 publications
3
49
0
3
Order By: Relevance
“…Animal experiments have shown that lower NK cell activity is associated with higher cancer incidence, while studies on NK cell activity on humans have found significantly lower NK activity among smokers compared to non-smokers (Ferson et al 1979;Ginns et al 1985;Phillips et al 1985;Talmadge et al 1980). Another study found that smoking decreased both the quantity and function of NK cells, and the quantity and function remained impaired after smoking cessation, while other white blood cell functions returned to normal (Tollerud et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have shown that lower NK cell activity is associated with higher cancer incidence, while studies on NK cell activity on humans have found significantly lower NK activity among smokers compared to non-smokers (Ferson et al 1979;Ginns et al 1985;Phillips et al 1985;Talmadge et al 1980). Another study found that smoking decreased both the quantity and function of NK cells, and the quantity and function remained impaired after smoking cessation, while other white blood cell functions returned to normal (Tollerud et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning immediate skin reactivity to common allergens [7,8] as well as specific antibody responses to inhaled antigens [9] and vaccinations [10], indicate depressed immune responses in smokers. There are several reports of decreased activity of natural killer (NK-) cells, both from peripheral blood [11,12] and the lung [13]. Results from functional studies of circulating T-lymphocytes are conflicting, with reports of increased [14], unchanged [15] and decreased [16,17] responses to mitogenic stimulation in vitro.…”
mentioning
confidence: 99%
“…Silverman et al 3) found the lymphocyte reactivity to PHA to be significantly higher in smokers under 40 years of age. In contrast to the diversity of lymphocyte reactivity in smokers, natural killer cell activity has been reported to be consistently depressed5, 10,11,16). A follow-up study in normal subjects following the cessation of smoking indicated that the increased count of lymphocytes and depressed natural killer cell activity were reversed9).…”
Section: Resultsmentioning
confidence: 99%